Managing Trouble Along a Continuum of Accountability: on Police Practices for Dealing with Less-Than-Competent Subjects - Buscariolli, André (The British journal of criminology, 2025)
This article uses conversation analysis to examine recordings of police encounters, focusing on how officers respond to routine forms of trouble emerging from civilians’ failure to comprehend and cooperate with their initiating actions. The analysis demonstrates how officers improvise methods to deal with their subjects’ troublesome responses to their queries and directives, treating civilians along a continuum from being purposefully uncooperative to lacking the interactional competence to comply with their projects. In the latter case, officers treat noncompliance as related to one’s status as "mentally disordered," adopting practices to progressively carve out islands of competence within which civilians are competent to cooperate or accountable for not doing so. Thus, officers’ orientation to a continuum of accountability shapes the encounter’s interactional trajectory toward more punitive or instructive outcomes.